Telmisartan inhibits the progression of cardiomyopathy in daunorubicin treated rats: the role of advanced glycation end products (Faculty of Medicine Universitas Indonesia, 2011)
Background: Anthracyclines have been reported to induce cardiotoxicity through mechanisms involving formation of advanced glycation end-products (AGEs), including pentosidine and Nє-(carboxymethyl) lysine (CML). We investigated the potential utility of telmisartan (TML), an angiotensin II receptor antagonists (ARB) on anthracycline-induced cardiotoxicity. Methods: Three groups of Sprague-Dawley rats were treated as follows: The first group received daunorubicin (DNR) 3 mg/kgBW every alternating day to reach a cumulative dose of 9 mg/kg DNR . The second group received DNR plus TLM at a dose10 mg/kgBW, by oral gavage for 6 weeks, and the third group served as control group (CTL) which only received vehicle of DNR. Mean blood pressure (MBP) peak left ventricular pressure (LVP), LV end-diastolic pressure (LVEDP), and intra-ventricular contractility (±dP/dt) were recorded by using Powerlab instrumentation. Ejection fraction (EF), and fractional shortening (FS) were measured by echocardiography. Expression of receptor of AGE (RAGE), pentosidine and CML were measured by immunohistochemistry and Western blot in LV tissue. Results: DNR treatment was associated with significant weakening of some hemodynamic parameters which could be reversed by TML (LVP: 124.3 ± 6.0; 111 ± 7; and 115.1 ± 5.4 mmHg, respectively in CTL, DNR and DNR-TLM groups; LVEDP: 7.5 ± 0.9; 10.7 ± 0.3; 8.7 ± 0.4 mmHg, respectively; +dP/dt: 6813 ± 541; 4800 ± 345; 5950 ± 398 mmHg/s, respectively). The same phenomenons were also observed on echocardiographic parameters (EF: 78.9 ± 1.8; 59.6 ± 1.4; 76.2 ± 2.75 %, resepectively; FS: 42.8 ± 1.7; 29.1 ± 1.3; 41 ± 2.7 %) respectively. Expression of RAGE as well as pentosidine and CML were increased in DNR-rats. TML treatment ameliorated these changes. Conclusion: These results suggested the role of AGE formation in DNR-induced cardiotoxicity and telmisartan could inhibit the progression of cardiac toxicity at least in part by reduction RAGE expressiom. (Med J Indones 2011; 20:255-62)